"And Africa will be saved!"? Nadenke oor die kerk, die sending en die nood van Sub-Sahara-Afrika - P. Verster (Acta Theologica)
Livingstone (1813-1873) with his emphasis on “Christianity, civilisation, commerce” had high expectations that Western influence would lead to total new conditions in Africa and the end of slave trade. Ludwig Krapf (1810-1881) was very sceptical concerning Western influence and of opinion that it would only lead to foreign solutions and new oppression in Africa. These two views are still present in the debate today. Through the years different exponents suggested that Africa should be given the opportunity to develop on its own while others suggested that massive help from developed countries was necessary. This article concurs with the views of Attie van Niekerk and suggests that elaborate developments will not succeed, but that the church should build up families as cornerstones of the community. In this sense Christ and his Kingdom should be proclaimed as the essence of mission.